ENGLISH LEARNING STRATEGIES IN ELEMENTARY SCHOOLS: CHALLENGES AND OPPORTUNITIES IN KAMPUS MENGAJAR PROGRAM - Alzar Putra Prastha; Larasati Larasati; Rolisda Yosintha (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2022)
Some research explores teachers' knowledge and views, proving that knowledge and beliefs play an important role in instructors' classroom decision-making. However, little study has been done to see how teachers' knowledge and opinions about how effective strategies affect implementation. Focus on the challenges and opportunities in Kampus Mengajar Program by implementing the English learning strategies in 16 Elementary School, this study aims to determine which technique is the most beneficial and what barriers participants face when implementing English learning in elementary schools as part of the Kampus Mengajar Program. The participants were English Department students' that participated in Kampus Mengajar Program at Tidar University consisting of 16 students. A questionnaire with open ended questions was used as the instrument in this survey. Playing games, using songs, using interactive media, and repetition were the four most commonly used strategies in teaching English language skills to young learners. These findings may be beneficial to those who teach English or work with young learners.